2015
DOI: 10.1371/journal.pone.0127498
|View full text |Cite
|
Sign up to set email alerts
|

Englerin A Agonizes the TRPC4/C5 Cation Channels to Inhibit Tumor Cell Line Proliferation

Abstract: Englerin A is a structurally unique natural product reported to selectively inhibit growth of renal cell carcinoma cell lines. A large scale phenotypic cell profiling experiment (CLiP) of englerin A on ¬over 500 well characterized cancer cell lines showed that englerin A inhibits growth of a subset of tumor cell lines from many lineages, not just renal cell carcinomas. Expression of the TRPC4 cation channel was the cell line feature that best correlated with sensitivity to englerin A, suggesting the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
150
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(156 citation statements)
references
References 40 publications
3
150
1
2
Order By: Relevance
“…2), which was first isolated in 2008 from the bark of the African plant Phyllanthus engleri, it was shown that the block of cell proliferation is correlated with the expression of the TRPC4 cation channel in sensitive cell lines suggesting TRPC4 to be the biologically relevant the target. This could be confirmed by electrophysiology experiments showing that englerin A can induce currents across the membranes of cells in presences of TRPC4, but not in its absence [7]. The same target was found in parallel by Waldmann et al following a similar approach [1].…”
Section: Cancersupporting
confidence: 56%
“…2), which was first isolated in 2008 from the bark of the African plant Phyllanthus engleri, it was shown that the block of cell proliferation is correlated with the expression of the TRPC4 cation channel in sensitive cell lines suggesting TRPC4 to be the biologically relevant the target. This could be confirmed by electrophysiology experiments showing that englerin A can induce currents across the membranes of cells in presences of TRPC4, but not in its absence [7]. The same target was found in parallel by Waldmann et al following a similar approach [1].…”
Section: Cancersupporting
confidence: 56%
“…TRPC4 is implicated in the regulation of microvascular permeability (5), renal cancer proliferation (6,7), neurotransmitter release (8), intestinal contraction and motility (9), neurite extension (10), epileptiform burst firing, and seizure-induced neurodegeneration (11). The channel mediates Na + and Ca 2+ influx, causing membrane depolarization and intracellular Ca 2+ concentration ([Ca 2+ ] i ) elevation, which in turn alter cell function (12).…”
mentioning
confidence: 99%
“…The Waldmann group reported that transfection of TRPC4 into HEK293T cells rendered the otherwise insensitive cells sensitive to englerin A. 65 On the basis of their inability to detect PKC θ in A498 cells or the sensitive Ewing’s sarcoma cell line A673, this group concluded that PKC θ could not be the target of englerin A, but that TRPC4/5 agonism was the relevant effect. 65 A recent report from Beech’s group found that englerin A cytotoxicity was mediated by influx of sodium, rather than of calcium, as had been previously proposed, and that both TRPC4 and TRPC1 must be part of the ion channel complex for cytotoxicity.…”
Section: Mechanism Of Action Studiesmentioning
confidence: 99%